STRUCTURE, FUNCTIONS AND IMPLEMENTATION FRAMEWORK OF THE WORLD TRADE ORGANIZATION (Scientific journal of the Fergana State University, 2024)
In the article, the authors describe the structure, functions and scope of the World Trade Organization (WTO), aswell as emphasize the role and importance of the organization's Secretariat in conducting the trade policy of thisorganization. It was emphasized that the specialists of the Republic of Uzbekistan should learn from the experience ofexperts working in the Secretariat of the organization